2013
DOI: 10.3846/16484142.2013.819034
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Modelling Traffic Related Emissions in Suburban Areas

Abstract: A methodology that integrates a computer program COPERT III for calculation of traffic emissions estimates, and a transportation modelling software CUBE VOYAGER was used to assess pollutant emissions for a suburban area, as a support for future transport planning strategies to be applied for any developing road network. COPERT III is used to obtain the carbon monoxide emission factors by accounting for the car fleet composition, characteristics and average speed. An aggregated emission parametric equation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Cerny et al showed suitable theoretical findings as a support for decision-making on economic sustainability and accessibility of public transport [11]. Tosa et al in their publications, investigated the occurrence of the vehicle engine pollution appearance taking into account velocity and street loading [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cerny et al showed suitable theoretical findings as a support for decision-making on economic sustainability and accessibility of public transport [11]. Tosa et al in their publications, investigated the occurrence of the vehicle engine pollution appearance taking into account velocity and street loading [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest to estimate road traffic pollutant emissions are the two models: MOVES-MOtor Vehicle Emissions Simulator (official tool recommended by the United States Environmental Protection Agency (U.S. EPA)) [41] and CORINAIR-CORe INventory AIR emissions, implemented in the COPERT IV © software [42,43]. The CORINAIR model takes into account many traffic and vehicle parameters, such as vehicle types, categories and population, yearly mileage (km/year), mean fleet mileage (km).…”
Section: Determination Of Consumption and Emissions In A Roundaboutmentioning
confidence: 99%